EFFECTIVENESS OF LAND TAX REVENUE FOR RURAL AND URBAN BUILDINGS IN PADANG BULAN VILLAGE, MEDAN BARU DISTRICT IN DECEMBER 2022-2024 - Elisha Stacia J Surbakti; Yetty Sembiring; Ardieansyah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The Rural and Urban Land and Building Tax (PBB-P2) is one of the main sources of regional revenue that is very important for the development of infrastructure and public services in Indonesia. To analyze the factors that affect the effectiveness of Rural and Urban Land and Building Tax (PBB-P2) revenue in Padang Bulan Village, Medan Baru District, from 2022 to 2024 in December. The research method used is a qualitative approach with secondary data collection in the form of annual PBB-P2 revenue reports. The results show that the effectiveness of PBB-P2 revenues increased from 2022 (51.83%) to 2023 (62.49%), but decreased slightly in 2024 (62.45%). Factors that affect the increase in revenue effectiveness include increasing taxpayer awareness, improving the tax collection system, or increasing the number of tax objects. Meanwhile, a small decline in 2024 was influenced by economic dynamics and tighter tax policies. This study provides recommendations to improve the tax administration system and community participation so that PBB-P2 revenues are more optimal in the future